Rapid Application Development on Web-Based Village Administration Application Design (SI-BANDID) Sei Limbat Village Kabupaten Langkat - Rizal, Chairul; Supiyandi; Fachri, Barany; Hasanuddin, Muhammad (Bahasa Indonesia, 2024)
The village is the government responsible for organizing and managing village-level government resources and organizing population management to provide services to the community. Although village officials are currently using computer media to provide data processing and population management services for their communities, they are still not utilizing it properly. The design of a web-based village administration service information system is a solution to the problem. This application allows the integration of village administration service information into the system through the use of the waterfall method in four stages: requirement analysis, system design, implementation, and system testing. One of the features of this administrative service application is the submission of letters by citizens, uploading of administrative letters submitted by citizens, employee registration, and citizen registration are features that can be accessed by the administration. With this application, the community and village staff gain additional benefits and value. This application is different from the previous service system it still uses manual methods to optimize the administration and processing of population data at the village office. It also makes it possible to present accurate population data and reports